Ageing with Smartphones in Urban China From the cultural to the digital revolution in Shanghai - Wang, Xinyuan (Ageing with Smartphones, 2023)
If we want to understand contemporary China, the key is through understanding the older generation. This is the generation in China whose life courses almost perfectly synchronised with the emergence and growth of the 'New China' under the rule of the Communist Party (1949). People in their 70s and 80s have double the life expectancy of their parents' generation. The current oldest generation in Shanghai was born in a time when the average household could not afford electric lights, but today they can turn their lights off via their smartphone apps. Based on 16-month ethnographic fieldwork in Shanghai, Ageing with Smartphones in Urban China tackles the intersection between the 'two revolutions' experienced by the older generation in Shanghai: the contemporary smartphone-based digital revolution and the earlier communist revolutions. We find that we can only explain the smartphone revolution if we first appreciate the long-term consequences of these people's experiences during the communist revolutions. The context of this book is a wide range of dramatic social transformations in China, from the Cultural Revolution to the individualism and Confucianism in Digital China. Supported by detailed ethnographic material, the observations and analyses provide a panoramic view of the social landscape of contemporary China, including topics such as the digital and everyday life, ageing and healthcare, intergenerational relations and family development, community building and grassroots organizations, collective memories and political attitudes among ordinary Chinese people.